2023
DOI: 10.3389/fpsyg.2023.1235846
|View full text |Cite
|
Sign up to set email alerts
|

Invariant and suboptimal trajectories of self-regulated learning during secondary school: implications focused on quality in higher education

Abstract: It has been shown that self-regulation of learning is a key variable for an adequate transition and adjustment from secondary school to tertiary education, and it is also associated with successful academic results; therefore, it is relevant to analyze its levels of development in the pre-university stage. The aim of this research was to evaluate the trajectories of self-regulation of learning in secondary school students. The method considered a longitudinal design and included a sample of 403 students from 9… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 67 publications
0
0
0
Order By: Relevance
“…Por tanto, se confirma que los programas de intervención que incluyen tecnologías en contextos educativos obtienen resultados positivos en el proceso de enseñanza-aprendizaje y favorecen el desarrollo de habilidades transversales en el estudiantado, en este caso, específicamente en el incremento de la autorregulación del aprendizaje. Esto es particularmente relevante, dado que la investigación reciente, ha demostrado que durante la educación secundaria el estudiantado presenta trayectorias invariantes de autorregulación del aprendizaje y que estas trayectorias están en niveles subóptimos (SÁEZ-DELGADO; MELLA-NORAMBUENA; LÓPEZ-ANGULO; SÁEZ et al, 2023), consecuentemente identificar que intervenciones basadas en tecnologías muestran un efecto en incremento de los procesos autorregulatorios, resulta prometedor.…”
Section: Discusión De Los Resultados Del Objetivo 2 Efectividad De La...unclassified
“…Por tanto, se confirma que los programas de intervención que incluyen tecnologías en contextos educativos obtienen resultados positivos en el proceso de enseñanza-aprendizaje y favorecen el desarrollo de habilidades transversales en el estudiantado, en este caso, específicamente en el incremento de la autorregulación del aprendizaje. Esto es particularmente relevante, dado que la investigación reciente, ha demostrado que durante la educación secundaria el estudiantado presenta trayectorias invariantes de autorregulación del aprendizaje y que estas trayectorias están en niveles subóptimos (SÁEZ-DELGADO; MELLA-NORAMBUENA; LÓPEZ-ANGULO; SÁEZ et al, 2023), consecuentemente identificar que intervenciones basadas en tecnologías muestran un efecto en incremento de los procesos autorregulatorios, resulta prometedor.…”
Section: Discusión De Los Resultados Del Objetivo 2 Efectividad De La...unclassified
“…Specifically, this study reported that adolescents aged 14–15 years had better metacognitive self-regulation than adolescents aged 17–18 years ( Bakracevic Vukman and Licardo, 2010 ). Additionally, studies have reported an overall decline in secondary school students’ metacognitive skills ( Ziegler and Opdenakker, 2018 ; Bardach et al, 2023 ; Sáez-Delgado et al, 2023 ).…”
Section: Introductionmentioning
confidence: 99%